Automated Tool for Health Utility Assessments: The Gambler II. Issue 1 (March 2020) - Adejare, Adeboye A.; Eckman, Mark H.
Background. The Gambler II is a web-based utility assessment tool supporting visual analogue scale (VAS), standard gamble (SG), and time trade-off (TTO) utility assessments. It contains novel features, including an easy to use project development authoring tool and use of multimedia clips for health state descriptions.Objectives. Evaluate the usability and understandability of the patient-facing side of The Gambler. Investigate the feasibility of using The Gambler and evaluate its impact on patient knowledge regarding the relevant health states.Materials and Methods. We used The Gambler to assess utilities on a convenience sample of 55 users for common long-term complications of type 2 diabetes mellitus: diabetic neuropathy, diabetic retinopathy, and diabetic foot infection requiring transmetatarsal amputation. Using VAS, SG, and TTO, we collected metadata, such as time spent on each assessment and the entire assessment process. We evaluated usability with an adaptation of the System Usability Scale survey and understandability. We evaluated impact on knowledge gained through knowledge assessments about these complications before and after use of The Gambler.Results. Overall satisfaction with The Gambler was high, 4.02 on a 5-point scale. Usability rated highly at 84.93 on a normalized scale between 0 and 100. Knowledge scores increased significantly following use of The Gambler from pretest mean of 68% to posttest mean of 76% ( P < 0.01). Average time using the software: ∼7½ minutes.Conclusions. The Gambler is an easy to use and understand computer-based tool for utility assessment. It is feasible to use within clinical encounters to support shared decision making, and it has unique features that make it a powerful tool for investigators interested in research on health utilities.